A multi-focus image fusion method based on watershed segmentation and IHS image fusion. (3rd April 2021) - Rashwan, Shaheera; Youssef, Amira; Youssef, Bayumy A. B.
ABSTRACT: High magnification optical cameras, such as microscopes or macro-photography, cannot capture an object that is totally in focus. In this case, image acquisition is done by capturing the object/scene with the camera using a set of images with different focuses, then fusing to produce an 'all-in-focus' image that is clear everywhere. This process is called multi-focus image fusion. In this paper, a method named Watershed on Intensity Hue Saturation (WIHS) is proposed to fuse multi-focus images. First, the defocused images are fused using IHS image fusion. Then the marker controlled watershed segmentation algorithm is utilized to segment the fused image. Finally, the Sum-Modified of Laplacian is applied to measure the focus of multi-focus images on each region and the region with higher focus measure is chosen from its corresponding image to compute the all-in- focus resulted image. The experiment results show that WIHS has best performance in quantitative comparison with other methods.